O sposobach pojmowania „cywilizacji” administracji publicznej oraz prawa administracyjnego - Gołaszewski, Piotr; Jagielski, Jacek (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
In the article, the authors attempt to systematize the problem of ways of understanding the concept of „civilization” ‒ respectively ‒ public administration and administrative law. The authors’ proposal includes a look at the phenomenon of „civilization” on the one hand as a „civilization” of public administration ‒ in its subject and subject matter, respectively, and on the other hand, as a „civilization” of administrative law, with its consolidated division into substantive law, systemic and procedural. In this convention, further considerations are presented in the article, which outline both general and specific problems, primarily in the field of administrative law, including the proposal of a separate view (not only in the context of the „civilization” of administrative law, but also broader research over this law) to events and legal-administrative relations, for which it is determined that the nature of a legal event does not prejudge the type (nature) of the legal relationship shaped by this event.
Keywords: integration; civilization; administrative; legal-administrative (s); task; form; material; process; relation; law; administration; science; event; legal; proceedings; civil law; public; systemic; civil